«Blagovist» Information Warning System for Railroad Crossings - Fedukhin, O.V.; Lutov, S.D.; Mukha А.А.; Cespedes Garcia, N.V.; Gedz, O.V. (Science and Innovation, 2024)
The article deals with traffic safety at ground railway crossings. An approach based on raising driver awareness via modern means of automation, computation, and communication has been considered. Blagovist information warning system for the railway crossings has been described.